Signet cell carcinoma of the colon in an 11-year-old child: A case report and review of literature - Pragya Singh; Lekshmi R; Sweety Gupta; Ravi Roushan Kumar; Shreyosi Mandal; Mridul Khanna; Satya Sree Balija; Ravi Hari Phulware; Manoj Gupta (Elsevier, 2024)
Background: Colon cancer is uncommon in children. This article reports a case of signet ring cell carcinoma in an 11-year-old child who presented with acute intestinal obstruction. Case report: An 11-year-old boy presented with progressive abdominal distension associated with constipation. The child underwent an abdominal X-ray in the erect position which revealed dilated bowel loops. Contrast enhanced computed tomography abdomen reported circumferential thickening involving 3.5 cm of the mid-transverse colon. The child underwent exploratory laparotomy which revealed mid transverse colon tumor. Tumor was resected with side-to-side anastomosis. Postoperative histopathology showed signet ring cell carcinoma. He was started on adjuvant chemotherapy. Conclusion: Surgery followed by adjuvant chemotherapy is the modality of treatment colorectal carcinoma. There are no screening guidelines available for the pediatric age group, however early diagnosis through colonoscopy screening can be considered to improve the prognosis.